The Study on Genetic Variability and Heritability in F4 Population of Rain-fed Rice (Oryza sativa L.) - Ferdous, Tasnia; Nur, Iffat Jahan; Romel, Monirul Haque; Bhuiyan, Shahidur Rashid (International Journal of Applied Sciences and Biotechnology, 2023)
Population establishment, selection, and evaluation are key components of plant breeding program. This study was designed to observe the genetic variability and the heritability of the selected yield component traits in F4 rice population. A field experiment was carried out with 16 F4 materials and 4 check varieties of Oryza sativa L. at Sher-e-Bangla Agricultural University, Dhaka to identify the suitable traits for the augmentation of rice yield. The F4 populations obtained from BR21×BR26, BR21× BRRI dhan28, BR 21× BRRI dhan29, BR24× BRRI dhan29, BR24× BRRI dhan36, BR26× BRRI dhan36 were utilized as breeding materials. Nine characters were considered i.e., days to 50% flowering, 80% maturity, plant height, tiller per panicle, panicle length(cm), filled grain per panicle, yield per plant(g), thousand-grain weight(g) and yield (t/ha). The selected genotypes were found significantly variable for all of the characters. The lowest days to maturity (92.00 days) were observed in G11 (BR21 × BRRI dhan29, F4, S7P2) following as G4 (BR21 × BRRI dhan29, F4, S1P2) (95.33 days) and G5 (BR21 ×BRRI dhan29, F4, S1P5) (96 days). The highest yield among F4 population was recorded in G6 (BR21 × BRRI dhan29, F4, S6P3) (6.08 t/ha) followed by G10 (BR21× BRRI dhan29, F4, S7P1) (5.30 t/ha) and G7 (BR21 × BRRI dhan29, F4, S6P8) (4.68ton/ha). All the traits showed remarkably higher phenotypic variances than the genotypic variances. Besides, all characters showed high heritability and higher PCV than the GCV. High heritability along with moderate to high genetic advance in percent mean is controlled by additive gene action which is better for selection. Int. J. Appl. Sci. Biotechnol. Vol 11(2): 99-105.